Preparation and characterization of blending sulfonated poly(ether ether ketone) with charged surface modifying macromolecules - Mohd. Norddin, M. N. A.; Ismail, A. F. (2007)
Charged surface modifying macromolecule (cSMM) end capped with sulfonic group was prepared and blended into sulfonated poly(ether ether ketone) (SPEEK). The modified membrane was characterized for polymer electrolyte membrane application; i.e. a SPEEK/cSMM blend membrane was compared to a SPEEK membrane and a Nafion 112 membrane for the thermal and mechanical stability, hydrophilicity and water uptake. Thermal and mechanical stability of the blend membrane were slightly reduced from that of the SPEEK membrane but still higher than that of the Nafion 112 membrane. The cSMM which was end–capped with sulfonic group has increased the total –SO3H group in the blend membrane. As a result, the blend membrane showed an increase in hydrophilicity and water uptake as compared to the pristine membrane. The addition of cSMM with an additional –SO3– charge has enabled the water uptake to be increased which is crucial to enhance the proton conductivity that of SPEEK. Moreover, the extra –SO3– can facilitate the transfer of proton better. This study found that cSMM is a good candidate as an additive for SPEEK in improving its function as polymer electrolyte membrane